Microgrid Policies: A Review of Technologies and Key Drivers of Thailand - Meenual, Thongchai; Usapein, Parnuwat (Frontiers in Energy Research, 2021)
Microgrids have been emerging and playing valuable roles in several parts of society, from academia of scholars to the energy supply industry of professional practitioners. A microgrid policy appeared in the Thailand 2015 energy development plan. There are many microgrids in Thailand. The first smart microgrid in Thailand is in active operation. Some microgrids are no longer functioning. Other microgrids continue to serve their customers. The remaining microgrid projects are in the process of development. Most present microgrids in Thailand are driven by public policy and legal flexibility. The objective of this research is to investigate the compatible microgrid technology in Thailand and explore the key drivers of microgrid policies in Thailand. The research methodology applied in this research includes data collection (i.e., a document study, interview, group discussion, and microgrid project participation and observation), as well as data analysis and conclusion. The findings of the research show that: in Thailand, the desired microgrid technologies are compatible with 1) inputs of potential local renewable energy resources of solar, wind, biomass, and mini-hydro, and 2) small gaps of human resource capabilities to deal with the technology utilization. The key drivers of the Thailand microgrid policy are 1) electricity access, 2) wealth creation and distribution, 3) environmental protection, and 4) technology development.